The relationship between maternal hemoglobin concentration in the first trimester of pregnancy and gestational diabetes - Narjes Noori; Alireza Ansari-Moghaddam; Saeed Toghi (Mashhad University of Medical Sciences, 2022)
Introduction: Diabetes is the most common endocrine disease in pregnancy and identifying the risk factors for gestational diabetes helps to identify women who are at risk for type 2 diabetes in the future. The present study was performed aimed to determine the relationship between maternal hemoglobin concentration in the first trimester of pregnancy and gestational diabetes in pregnant women. Methods: This retrospective study was performed on 300 cases of pregnant women who referred to medical centers of Zahedan in 2017-2019. The information checklist was used to collect demographic characteristics of research samples such as age, height, weight and number of pregnancies and deliveries, maternal hemoglobin and FBS concentrations at the first visit to the relevant centers and GCT levels in 24 to 28 weeks of pregnancy. Data were analyzed by SPSS statistical software (version 25) and Independent t-test and ANOVA tests. P<0.05 was considered statistically significant. Results: Out of 300 women in the statistical population, 113 (37.7%) had gestational diabetes and 187 (62.3%) were healthy in terms of diabetes. Of the subjects, 103 (34.3%) had hemoglobin concentrations greater than 13, 42 (14%) had hemoglobin concentrations 12.4 to 13, 79 (26.3%) had hemoglobin concentrations between 11.6 to 12.3, and 76 (25.3%) had hemoglobin concentrations less than 11.5. The mean hemoglobin level in diabetic pregnant women was 13.71 ± 0.61 g/dl and in healthy women was 11.80 ± 0.52 g/dl, and the difference was statistically significant (P <0.001). There was also a positive and significant correlation between hemoglobin and fasting blood sugar levels (P <0.001). Conclusion: High hemoglobin level (more than 13 g/dl) in the first trimester of pregnancy is significantly and directly related to gestational diabetes, therefore it can be considered as a risk factor for gestational diabetes.